Are community midwives addressing the inequities in access to skilled birth attendance in Punjab, Pakistan? Gender, class and social exclusion - Mumtaz Zubia; O'Brien Beverley; Bhatti Afshan; Jhangri Gian S (BMC, 2012)
Abstract Background Pakistan is one of the six countries estimated to contribute to over half of all maternal deaths worldwide. To address its high maternal mortality rate, in particular the inequities in access to maternal health care services, the government of Pakistan created a new cadre of community-based midwives (CMW). A key expectation is that the CMWs will improve access to skilled antenatal and intra-partum care for the poor and disadvantaged women. A critical gap in our knowledge is whether this cadre of workers, operating in the private health care context, will meet the expectation to provide care to the poorest and most marginalized women. There is an inherent paradox between the notions of fee-for-service and increasing access to health care for the poorest who, by definition, are unable to pay. Methods/Design Data will be collected in three interlinked modules. Module 1 will consist of a population-based survey in the catchment areas of the CMW's in districts Jhelum and Layyah in Punjab. Proportions of socially excluded women who are served by CMWs and their satisfaction levels with their maternity care provider will be assessed. Module 2 will explore, using an institutional ethnographic approach, the challenges (organizational, social, financial) that CMWs face in providing care to the poor and socially marginalized women. Module 3 will identify the social, financial, geographical and other barriers to uncover the hidden forces and power relations that shape the choices and opportunities of poor and marginalized women in accessing CMW services. An extensive knowledge dissemination plan will facilitate uptake of research findings to inform positive developments in maternal health policy, service design and care delivery in Pakistan. Discussion The findings of this study will enhance understanding of the power dynamics of gender and class that may underlie poor women's marginalization from health care systems, including community midwifery care. One key outcome will be an increased sensitization of the special needs of socially excluded women, an otherwise invisible group. Another expectation is that the poor, socially excluded women will be targeted for provision of maternity care. The research will support the achievement of the 5th Millennium Development Goal in Pakistan.